Data Analysis as a Method to gather Data to study the Relation between Fundamental Rights and Rule of Law - Antoinette Muntjewerff; Kirsten Van Loo (Talenta Publisher, 2018)
The research described here involves the relation between fundamental rights and the rule of law. In the end we want to find out what meaning is attributed to ‘rule of law’ by the European Court of Human Rights. In this article we describe our method to gather the data we need to be able to perform an analysis of the reasoning process by the Court.